2018
DOI: 10.22159/ajpcr.2018.v11i11.29079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Osteopathy in Patients With Beta-Thalassemia Major Using Different Iron Chelation Therapies

Abstract: Objective: We aim to assess the bone mineral density (BMD) and bone biochemical parameters in Iraqi patients with β-thalassemia major (β-TM).Methods: Dual-energy X-ray absorptiometry scan was used to evaluate bone density and interpreted about Z-score which compares to the BMD of age-, sex-, and ethnicity-matched reference population. Biochemical parameters such as calcium, 25-OH Vitamin D, parathyroid hormone, and serum ferritin (SF) evaluated.Results: No statistical difference in SF between pediatrics and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The prevalence of osteopenia and osteoporosis in thalassemic patients is 30-50%, and related fractures are reported in >20% of adult patients with thalassemia. 14,15 The study participants' mean age was 19.59±7.59 years, similar to Shawkat et al study, 16 while other studies reported a lower/higher mean age than this study. [17][18][19] Most of the patients in this study were females, which is consistent with the study conducted in Iran by Bordbar et al 20 but it is not agreed with another study conducted in Iraq.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of osteopenia and osteoporosis in thalassemic patients is 30-50%, and related fractures are reported in >20% of adult patients with thalassemia. 14,15 The study participants' mean age was 19.59±7.59 years, similar to Shawkat et al study, 16 while other studies reported a lower/higher mean age than this study. [17][18][19] Most of the patients in this study were females, which is consistent with the study conducted in Iran by Bordbar et al 20 but it is not agreed with another study conducted in Iraq.…”
Section: Discussionsupporting
confidence: 87%
“…Bone markers are produced during the bone remodelling process which involved bone formation markers, bone resorption markers, and bone turnover regulators. These markers may be enzymes, © Pharmascope Publications | International Journal of Research in Pharmaceutical Sciences proteins or byproducts during the bone remodelling process (Liu and Webster, 2016;Shawkat et al, 2018). Deoxypyridinoline is a molecule act to stabilise collagen via cross-linking between collagen peptides (Seibel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Migraines are challenging to investigate in laboratory animals due to the occurrence of pain without tissue damage and the constraints of current behavioral tests (19). Several studies have employed the reduction of activity (such as locomotors activity, eating, and rearing) to evaluate discomfort caused by headaches in rodents (20)(21)(22)(23). In addition, migraines are present in other animal models like dogs (24).…”
Section: Hamzah and Kassabmentioning
confidence: 99%